Geochemical enrichment of metals in sediments and their relation with the organic carbon. Issue 1 (2nd January 2017) - Fernandes, Felippe; Poleto, Cristiano
ABSTRACT: This article aims to assess the concentrations of zinc (Zn) and nickel (Ni) and the organic matter (OM) content in different depth samples of sediments produced in this river basin of the Mãe d'Água dam. The sampling was carried out in June 2014, and four sediment cores in pre-defined points of the dam were sampled. A core sampler 'Piston Core' was used for the extraction of sediment cores. The sediments with fraction less than 63 μm were destined to the chemical analysis for the verification of the presence and concentration of trace elements: Ni and Zn. The acid digestion methodology employed is the EPA 3050, adopted by the US Environment Protection Agency, and the analyses were carried out in duplicates and for quality control we used two reference materials of the US Geological Survey: Green River Shale (SGR-1b) and Cody Shale (SCO-1). With the results obtained, all samples showed concentrations of Zn and Ni above the local background value and growth patterns, demonstrating the existence of enrichment of the sediments by these elements. The levels of OM when correlated at concentrations of Zn and Ni showed the growing enrichment in the sediment cores analysed, confirming the high affinity of these elements with the sediment compounds of fraction organic.